Layered structure with high dielectric constant for use with active matrix backplanes
Patent Information
- Application Number
- JP2024215478
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-05-03
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
Smart Images

Figure 2025038033000002 
Figure 2025038033000003 
Figure 2025038033000004
Abstract
Description
[Background technology]
[0001] This application claims priority to U.S. Provisional Application No. 62 / 843,082, filed May 3, 2019. All patents and patent applications referenced herein are incorporated by reference in their entirety.
[0002] An electrophoretic display typically comprises a layer of electrophoretic material and at least two other layers (one of these two layers is an electrode layer) disposed on opposite sides of the electrophoretic material. In most such displays, both layers are electrode layers, and one or both of the electrode layers are patterned to define the pixels of the display. Typically, one electrode layer has the form of a single continuous electrode, and the other electrode layer is patterned into a matrix of pixel electrodes, each of which defines one pixel of the display. In one example, the electrophoretic medium is encapsulated in microcapsules, which are dispersed in a binder coated on a flexible substrate comprising indium tin oxide (ITO) or a similar conductive coating on a plastic film (peelable), which acts as one electrode of the final display, and the capsule / binder coating is dried to form a coherent layer of electrophoretic medium firmly adhered to the substrate. Separately, a backplane is prepared containing an array of pixel electrodes and an appropriate arrangement of conductors for connecting the pixel electrodes to a drive circuitry. To form the final display, the substrate with the encapsulant / binder layer thereon is laminated to the backplane using a lamination adhesive.
[0003] The lamination adhesive(s) and binder are engineered to have a particular conductivity such that the electrophoretic particles behave predictably. For example, in a black and white electrophoretic display, when the display is addressed to achieve a particular gray state, the gray state should not drift in measured reflectance over time. In reality, however, the layered stack acts as a capacitor, and the optical state drifts slightly as stored electrical energy discharges from the display stack. Such variations are often not perceptible in black and white electronic readers, but in advanced applications such as full-color electrophoretic displays using dithered colors, the perceived image may vary significantly due to capacitive discharge. As the color pigments shift with capacitive decay, for example, a pale orange hue may take on a green hue, which is immediately noticeable to many viewers. To avoid such limitations, it may be beneficial to have better tools to control the dielectric capacitance within a stack of electrophoretic materials. A further advantage may be the reduction of electrochemical reactions between conductive materials, such as pixel electrodes, and trace materials, such as salts, that may be introduced into the adhesive layer or electrophoretic medium during processing.
[0004] The electric field experienced by the electrophoretic fluid in an electrophoretic display depends on the drive waveform and (a) the capacitances of the various layers that make up the display, and more importantly (b) the capacitances of the interfaces between these layers. When the display is driven and then grounded, the charge stored in these capacitors is depleted with a time constant that depends on the capacitance and resistance through which the return current flows. If this time constant is too short, an excessively fast discharge can cause the charged pigments to move in the opposite direction to the direction in which they were originally driven. This phenomenon is called "optical kickback". It would be preferable to engineer the capacitances of the various layers and interfaces in the display, in particular the interfaces between the ionically conductive layer of the display and at least one of the drive electrodes, so that this time constant can be controlled.
[0005] One solution to overcome optical kickback is to drive the electrophoretic fluid with a so-called "DC balanced" waveform. As discussed in U.S. Patent Nos. 6,531,997 and 6,504,524, if the method used to drive the display does not result in a zero or near-zero net time-averaged applied electric field across the electro-optic medium, problems can be encountered and the working life of the display can be reduced. Driving methods that result in a zero net time-averaged applied electric field across the electro-optic medium are conveniently referred to as "direct current balanced" or "DC balanced". Driving waveforms that are not DC balanced are typically referred to as "DC unbalanced". Most electrophoretic displays are designed to operate with DC balanced waveforms due to concerns about operating life and optical effects such as kickback.
[0006] In addition to electrophoretic displays, control of dielectric capacitance is also important in electrowetting applications such as electrowetting displays and digital microfluidics (alternatively referred to as electrowetting-on-dielectric or "EWoD"). EWoD techniques allow sample preparation, assays, and synthetic chemistries to be performed with both minute amounts of sample and reagents. (A 2012 overview of electrowetting technologies is available in "Digital Microfluidics," 2012.) Annu. Rev. Anal. Chem.(2012, 5:413-40, which is incorporated herein by reference in its entirety). Such EWoD devices may be constructed with segmented electrodes, whereby 10-20 electrodes are directly driven with a voltage controller. Alternatively, EWoD devices may incorporate active matrix devices (known as active matrix EWoD, also known as AM-EWoD) that contain thousands, hundreds of thousands, or even millions of addressable electrodes. In active matrix, the electrodes are typically controlled by thin film transistors (TFTs), and droplet motion is computer programmable such that AM-EWoD arrays may be used as general-purpose devices that allow considerable freedom to control multiple droplets and perform simultaneous analytical processes. In some cases, the electrodes of EWoD systems are coated with a high dielectric constant material, such as silicon nitride, to increase the local field strength at the pixel, thus facilitating better droplet control. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] U.S. Patent No. 6,531,997 [Patent Document 2] U.S. Patent No. 6,504,524 [Non-patent literature]
[0008] [Non-Patent Document 1] Wheeler,Digital Microfluidics,Annu. Rev. Anal. Chem.,2012,5:413-40 Summary of the Invention [Means for solving the problem]
[0009] This application discloses preferred dielectric layer structures that can be used for several applications including semiconductor electronics, electro-optic displays, and digital microfluidic devices. The described dielectric layers have good surface smoothness, are largely pinhole-free, and achieve high dielectric constants with reduced chemical reactivity.
[0010] In one instance, the invention includes a layered dielectric comprising a first layer (known as a barrier layer), a second layer (known as a thick layer), and a third layer (known as a capping layer), with the second layer disposed between the first and third layers. The first layer comprises aluminum oxide or hafnium oxide and has a thickness between 9 nm and 80 nm. The second layer comprises tantalum oxide or hafnium oxide and has a thickness between 40 nm and 250 nm. The third layer comprises tantalum oxide or hafnium oxide and has a thickness between 5 nm and 60 nm. In one embodiment, the first layer comprises Al2O3, the second layer comprises HfO2, and the third layer comprises Ta2O5. In another embodiment, the first layer comprises Al2O3, the second layer comprises Ta2O5, and the third layer comprises HfO2. Typically, the first layer is 20-40 nm thick, and / or the second layer is 100-150 nm thick, and / or the third layer is 10-35 nm thick. In some embodiments, the dielectric strength of the layered dielectric is greater than 6 MV / cm.
[0011] The dielectric layer of the present invention can be deposited on a substrate, for example a substrate including a plurality of electrodes disposed between the substrate and the layered dielectric. In some embodiments, the electrodes are arranged in an array, with each electrode associated with a thin film transistor (TFT). In some embodiments, a hydrophobic layer is deposited on the third layer, i.e., on top of the dielectric stack. In some embodiments, the hydrophobic layer is a fluoropolymer, which is 10-50 nm thick, and can be deposited using spin coating or another coating method.
[0012] Also described herein is a method for making a layered dielectric of the type described above. The method includes providing a substrate, depositing a first layer using atomic layer deposition (ALD), depositing a second layer using sputtering, and depositing a third layer using ALD. (The first layer is deposited on the substrate, the second layer is deposited on the first layer, and the third layer is deposited on the second layer). The first ALD layer typically comprises aluminum oxide or hafnium oxide and has a thickness of 9 nm to 80 nm. The second sputtered layer typically comprises tantalum oxide or hafnium oxide and has a thickness of 40 nm to 250 nm. The third ALD layer typically comprises tantalum oxide or hafnium oxide and has a thickness of 5 nm to 60 nm. In some embodiments, the atomic layer deposition includes plasma-assisted atomic layer deposition. In some embodiments, the sputtering includes radio frequency magnetron sputtering. In some embodiments, the atomic layer deposition process includes introducing Al(CH3)3, Ta[(N(CH3)2)3NC(CH3)3], or Hf(N(CH3)2)4, and generating an oxygen plasma. In some embodiments, the ALD process is completed at a pressure of less than one atmosphere. In some embodiments, the method further includes spin-coating a hydrophobic material onto the third layer.
[0013] The dielectric layers described herein may be used in electrophoretic displays to improve the lifetime of the display, for example by reducing electrochemical reactions between adhesive components, binders, primers, or electrophoretic media and the driving electrodes, for example, active matrix backplanes or top electrodes, for example, layers of PET-ITO. Intentional inclusion of a dielectric layer in an electrophoretic display typically causes reduced optical performance, but it has been found that in displays driven with DC unbalanced waveforms, acceptable optical performance can be achieved with regular active grounding of the electrodes between updates. The overall update time for pixels in an image can be reduced because (a) no time is required for DC balancing pulses, and (b) DC balancing pulses may bias the optical state of the display in the opposite direction to the intended color and require additional waveform time to overcome. DC unbalanced waveforms lead to the accumulation of residual voltages, which can be dissipated during grounding after driving.
[0014] Such a dielectric layer can be incorporated into an electrophoretic display, for example an electrophoretic display comprising a light-transmitting electrode, a dielectric layer, an electrophoretic layer, and a back electrode. Typically, the electrophoretic layer comprises a first set of light-scattering particles and two additional sets of particles having optical properties different from the first set of light-scattering particles. In some embodiments, the dielectric layer is 10 nm thick to 100 nm thick, i.e., 25 nm thick to 75 nm thick. The dielectric layer may comprise aluminum oxide, hafnium oxide, tantalum oxide, or silicon nitride, and the dielectric layer may be formed by a combination of both atomic layer deposition and sputtering. In some embodiments, the electrophoretic display also comprises an adhesive layer. In some embodiments, the electrophoretic layer comprises four sets of charged pigment particles. The four sets of charged pigment particles may be dispersed in a non-polar solvent. The four sets of charged pigment particles can be white, cyan, magenta, and yellow, or white, black, red, and yellow, or white, blue, red, and yellow, in some embodiments, two of the sets of particles are positively charged and two of the sets of particles are negatively charged.
[0015] The present invention additionally includes a method of driving an electrophoretic display with a DC unbalanced waveform. The method includes providing an electrophoretic display, providing a voltage source, and driving the electrophoretic layer with a DC unbalanced waveform including both a drive portion and a ground portion. The electrophoretic display includes a light-transmissive electrode, a dielectric layer, an electrophoretic layer, and a back electrode. In some embodiments, the drive portion occurs during a first period, and the ground portion occurs during a second period, the second period being the same length or longer than the first period. In some embodiments, the dielectric layer is 10 nm thick to 100 nm thick, i.e., 25 nm thick to 75 nm thick. The dielectric layer may include aluminum oxide, hafnium oxide, tantalum oxide, or silicon nitride. In some embodiments, the dielectric layer is formed using both atomic layer deposition and sputtering. In some embodiments, the electrophoretic display additionally includes an adhesive layer. In some embodiments, the electrophoretic layer includes at least two charged pigment particles dispersed in a non-polar solvent, for example, the electrophoretic layer may include four charged pigment particles. In embodiments with four charged pigment particles, the particles may be white, cyan, magenta, and yellow, or white, black, red, and yellow, or white, blue, red, and yellow. The present invention provides, for example: (Item 1) A layered dielectric material, a first layer comprising aluminum oxide or hafnium oxide and having a thickness of 9 nm to 80 nm; a second layer comprising tantalum oxide or hafnium oxide and having a thickness of 40 nm to 250 nm; a third layer comprising tantalum oxide or hafnium oxide and having a thickness of 5 nm to 60 nm; wherein the second layer is disposed between the first layer and the third layer. (Item 2) Item 2. The layered dielectric of item 1, wherein the first layer comprises Al2O3, the second layer comprises HfO2, and the third layer comprises Ta2O5. (Item 3) Item 2. The layered dielectric of item 1, wherein the first layer comprises Al2O3, the second layer comprises Ta2O5, and the third layer comprises HfO2. (Item 4) 2. The layered dielectric according to item 1, wherein the first layer is 20 to 40 nm thick. (Item 5) 2. The layered dielectric according to claim 1, wherein the second layer is 100 to 150 nm thick. (Item 6) 2. The layered dielectric according to item 1, wherein the third layer is 10 to 35 nm thick. (Item 7) Item 1. A substrate comprising the layered dielectric material of item 1. (Item 8) Item 8. The substrate of item 7, further comprising a plurality of electrodes disposed between the substrate and the layered dielectric of item 1. (Item 9) 9. The substrate of claim 8, wherein the electrodes are arranged in an array, each electrode being associated with a thin film transistor (TFT). (Item 10) 10. The substrate of claim 9, further comprising a hydrophobic layer deposited on the third layer. (Item 11) Item 11. The substrate according to item 10, wherein the hydrophobic layer is 10 to 50 nm thick. (Item 12) 2. The layered dielectric of claim 1, wherein the dielectric strength of the layered dielectric is greater than 6 MV / cm. (Item 13) 1. A method of making a layered dielectric comprising the steps of: Providing a substrate; depositing a first layer comprising aluminum oxide or hafnium oxide using atomic layer deposition, the first layer having a thickness between 9 nm and 80 nm; depositing a second layer comprising tantalum oxide or hafnium oxide using sputtering, the second layer having a thickness between 40 nm and 250 nm; depositing a third layer comprising tantalum oxide or hafnium oxide using atomic layer deposition, the third layer having a thickness of 5 nm to 60 nm; A method comprising: (Item 14) 1. An electrophoretic display comprising: A light-transmitting electrode; A dielectric layer; an electrophoretic layer comprising a first set of light scattering particles and two additional sets of particles, the two additional sets of particles having different optical properties from each other and from the first set of light scattering particles; A back electrode; An electrophoretic display comprising: (Item 15) Item 15. An electrophoretic display according to item 14, wherein the dielectric layer is between 10 nm thick and 100 nm thick. (Item 16) Item 15. An electrophoretic display according to item 14, wherein the dielectric layer is between 25 nm thick and 75 nm thick. (Item 17) Item 15. An electrophoretic display as described in item 14, wherein the dielectric layer comprises aluminum oxide, hafnium oxide, tantalum oxide, or silicon nitride. (Item 18) Item 15. An electrophoretic display as described in item 14, wherein the electrophoretic layer comprises four sets of charged pigment particles. (Item 19) 1. A method of driving an electrophoretic display with a DC unbalanced waveform, comprising: 1. An electrophoretic display comprising: A light-transmitting electrode; A dielectric layer; An electrophoretic layer; Back electrode and and Providing a voltage source; driving the electrophoretic layer with a DC unbalanced waveform including both a drive portion and a ground portion; A method comprising: (Item 20) 20. The method of claim 19, wherein the drive portion occurs for a first period of time and the ground portion occurs for a second period of time, the second period of time being the same length as or longer than the first period of time. [Brief description of the drawings]
[0016] [Figure 1A] FIG. 1A illustrates the use of a dielectric layer with an encapsulated electrophoretic medium.
[0017] [Figure 1B] FIG. 1B illustrates the use of a dielectric layer with an electrophoretic medium contained within a microcell.
[0018] [Figure 1C] FIG. 1C illustrates the use of a dielectric layer with an encapsulated electrophoretic medium.
[0019] [Figure 1D] FIG. 1D illustrates the use of a dielectric layer with an electrophoretic medium contained within a microcell.
[0020] [Figure 1E] FIG. 1E illustrates the use of a dielectric layer with an encapsulated electrophoretic medium.
[0021] [Figure 1F] FIG. 1F illustrates the use of a dielectric layer with an electrophoretic medium contained within a microcell.
[0022] [Diagram 2] Figure 2 depicts the movement of an aqueous phase droplet between adjacent electrodes by providing different charge states on the adjacent electrodes. Typically, a dielectric layer and a hydrophobic layer are disposed between the pixel electrode and the droplet.
[0023] [Diagram 3]FIG. 3 is a simplified circuit diagram showing how an EWoD device can be driven in a manner similar to an active matrix of pixel electrodes for a display.
[0024] [Figure 4] FIG. 4 illustrates an embodiment of a dielectric layer on a substrate.
[0025] [Diagram 5] FIG. 5 illustrates an embodiment of a dielectric layer on a substrate containing pixel electrodes.
[0026] [Figure 6] FIG. 6 illustrates the steps for creating the dielectric layer.
[0027] [Figure 7] FIG. 7 shows atomic force microscopy images of each of the three layers in the dielectric stack of the present invention.
[0028] [Figure 8] FIG. 8 shows an example height measurement as a function of linear position at the dotted line across the AFM image of FIG.
[0029] [Figure 9A] FIG. 9A illustrates a first model circuit that can be used to calculate a baseline for the remnant voltage response in an electrophoretic display.
[0030] [Figure 9B] FIG. 9B illustrates a second model circuit that can be used to calculate the benefits of adding one or more dielectric layers to an electrophoretic display.
[0031] [Figure 10A] FIG. 10A is the calculated voltage response for each component C1-C4 of the model circuit of FIG. 9A when the stack is driven with the waveform "STACK."
[0032] [Figure 10B] FIG. 10B is the calculated voltage response for each component C1-C5 of the model circuit of FIG. 9B when the stack is driven with the waveform "STACK."
[0033] [Figure 11A] FIG. 11A shows the remnant voltage measured on test cells having various SiNi dielectric layer thicknesses when driven with a 100% drive / ground duty cycle.
[0034] [Figure 11B] FIG. 11B shows the remnant voltage measured on test cells having various SiNi dielectric layer thicknesses when driven with a 50% drive / ground duty cycle.
[0035] [Figure 11C] FIG. 11C shows the remnant voltage measured on test cells having various SiNi dielectric layer thicknesses when driven with a 25% drive / ground duty cycle.
[0036] [Figure 12] FIG. 12 shows the measured resistive current density as a function of drive voltage in an electrophoretic display having front electrodes with (blocking) or without (non-blocking) a dielectric layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0037] This application details structures and methods for making layered dielectric materials with high (greater than k=5) dielectric constants. The layered dielectrics described herein are excellent materials for modifying the electric field interactions between, for example, an electrophoretic medium and top and bottom electrodes. Furthermore, the layered dielectrics have very few pinholes, so there is less current leakage and less unwanted electrochemical properties in the resulting devices.
[0038] The advantages of high-k dielectric materials are appreciated in the fields of materials science and electrical engineering. The dielectric constant k generally describes the ability of a material to store electrical energy in an electric field. Generally, as the dielectric constant of a material increases, the amount of electric field passing through the material decreases. Thus, high dielectric constant materials are used to make the electric field constant and prevent concentrated electric field gradients that can cause unwanted electrical switching of electrical elements such as transistors. The continuity of the dielectric layer is very important because variations in thickness or composition can create paths for short circuits and dielectric breakdown.
[0039] When used with an electrophoretic display, the dielectric layer is provided to cover the transparent common electrode of the electrophoretic display, or to cover the pixelated backplane electrode, or both. The dielectric layer performs two functions. First, it acts as a barrier to ion and electron transport. Reducing ion and electron transport results in reduced electrochemical properties at the electrode interface, thereby mitigating degradation of the electrode material when the display is driven. Second, the dielectric layer separates the display electrodes and the conductive display layer, and therefore provides a capacitive element that can be used to control the accumulation and discharge of residual voltages in the display. These two features are particularly important in displays driven with DC unbalanced waveforms.
[0040] One type of electro-optic display that has been the subject of intensive research and development for many years is the particle-based electrophoretic display, in which a plurality of charged particles move through a fluid under the influence of an electric field. Electrophoretic displays can have attributes of good brightness and contrast, wide viewing angles, state bistability, and low power consumption compared to liquid crystal displays. Nevertheless, problems with the long-term image quality of these displays have prevented their widespread use. For example, the particles that make up electrophoretic displays tend to settle, resulting in inadequate useful life for these displays.
[0041] An electrophoretic display typically comprises a layer of electrophoretic material and at least two other layers (one of these two layers is an electrode layer) disposed on opposite sides of the electrophoretic material. In most such displays, both layers are electrode layers, and one or both of the electrode layers are patterned to define the pixels of the display. For example, one electrode layer may be patterned into elongated row electrodes and the other into elongated column electrodes extending at right angles to the row electrodes, the pixels being defined by the intersections of the row and column electrodes. Alternatively, and more commonly, one electrode layer has the form of a single continuous electrode and the other electrode layer is patterned into a matrix of pixel electrodes, each of which defines one pixel of the display. In another type of electrophoretic display intended for use with a stylus, print head, or similar movable electrode that is separate from the display, only one of the layers adjacent to the electrophoretic layer comprises an electrode; the layer on the opposite side to the electrophoretic layer is typically a protective layer intended to prevent the movable electrode from damaging the electrophoretic layer.
[0042] As used herein, electrophoretic media includes charged particles that vary in color, reflective or absorbing properties, charge density, and mobility in an electric field (measured as zeta potential). Particles that absorb, scatter, or reflect light, either in a broad band or at selected wavelengths, are referred to herein as colored or pigment particles. Various materials other than pigments (in the strict sense of the term, which means insoluble colored materials) that absorb or reflect light, such as dyes or photonic crystals, can also be used in the electrophoretic media and displays of the present invention. For example, an electrophoretic medium may include a fluid, a plurality of first particles and a plurality of second particles dispersed in the fluid, where the first particles and the second particles carry charges of opposite polarity, the first particles are light scattering particles, and the second particles have one of three subtractive primary colors, and a plurality of third particles and a plurality of fourth particles dispersed in the fluid, where the third particles and the fourth particles carry charges of opposite polarity, the third particles and the fourth particles each have a different subtractive primary color from each other and from the second particles, and where the electric field required to separate aggregates formed by the third particles and the fourth particles exceeds that required to separate aggregates formed from any other two types of particles.
[0043] The electrophoretic medium of the present invention may contain any of the additives used in the prior art electrophoretic media, for example, as described in the E INK and MIT patents and applications mentioned above.Thus, for example, the electrophoretic medium of the present invention typically comprises at least one charge control agent for controlling the charge on various particles, and the fluid may have dissolved or dispersed therein a polymer having an average molecular weight of more than about 20,000 and essentially non-absorbent on the particles to improve the bistability of the display, as described in the aforementioned U.S. Patent No. 7,170,670.
[0044] In one embodiment, the present invention uses light scattering particles, which are typically white, and three substantially non-light scattering particles. Of course, there is no such thing as a completely light scattering particle or a completely non-light scattering particle, and the minimum light scattering degree of the light scattering particles and the maximum acceptable light scattering degree acceptable in the substantially non-light scattering particles used in the electrophoresis of the present invention may vary somewhat depending on factors such as the exact pigments used, their colors, and the user's ability or application to tolerate some deviation from the ideal desired color. The scattering and absorption properties of the pigments can be assessed by measuring the diffuse reflectance of a sample of the pigment dispersed in an appropriate matrix or liquid against a white and dark background. The results from such measurements can be interpreted according to several models well known in the art, such as the one-dimensional Kubelka-Munk process. In the present invention, it is preferred that the white pigment exhibits diffuse reflectance at 550 nm when measured over at least a 5% black background when the pigment is dispersed approximately isotropically at 15% by volume in a 1 μm thick layer comprising the pigment and a liquid with a refractive index less than 1.55. The yellow, magenta, and cyan pigments preferably exhibit diffuse reflectance at 650 nm, 650 nm, and 450 nm, respectively, when measured over a black background of less than 2.5% under the same conditions. (The wavelengths selected above for measuring the yellow, magenta, and cyan pigments correspond to the spectral regions of minimal absorption by these pigments.) Colored pigments that meet these criteria are hereinafter referred to as "non-scattering" or "substantially non-light scattering." Specific examples of suitable particles are disclosed in U.S. Patent No. 9,921,451, which is incorporated herein by reference.
[0045] Alternative particle sets including one absorbing particle with four sets of reflective particles, or three or four sets of different reflective particles (i.e., such as those described in U.S. Pat. Nos. 9,922,603 and 10,032,419, incorporated herein by reference) may also be used. For example, the white particles may be formed from inorganic pigments such as TiO2, ZrO2, ZnO, Al2O3, Sb2O3, BaSO4, PbSO4, or equivalent, while the black particles may be formed from CI pigment black 26 or 28 or equivalent (e.g., manganese ferrite black spinel or copper chromite black spinel) or carbon black. The third / fourth / fifth type particles may be of a color such as red, green, blue, magenta, cyan, or yellow. Pigments for this type of particle may include, but are not limited to, CI pigment PR254, PR122, PR149, PG36, PG58, PG7, PB28, PB15:3, PY138, PY150, PY155, or PY20. Specific examples include Clariant Hostaperm Red D3G70-EDS, Hostaperm Pink E-EDS, PV Fast Red D3G, Hostaperm Red D3G70, Hostaperm Blue B2G-EDS, Hostaperm Yellow H4G-EDS, Hostaperm Green GNX, BASF Irgazine Red L3630, Cinquasia Red L4100HD, and Irgazin Red L3660HD, Sun Chemical Phthalocyanine Blue, Phthalocyanine Green, Diarylide Yellow, or Diarylide AAOT Yellow.
[0046] Typical electrophoretic displays are driven with an impulse balanced waveform (known as a DC balanced waveform), as described, for example, in U.S. Pat. No. 7,119,772. The purpose of impulse balance is to limit the build-up of residual voltage and protect the display electrodes from electrochemical damage. However, providing DC balance can seriously impair the waveform, especially for color displays, such as those disclosed in U.S. Pat. No. 10,276,109. As discussed in U.S. Pat. No. 10,276,109 with reference to FIG. 1, color display waveforms typically include a first phase that provides DC balance to the overall update waveform. That is, the first phase delivers a net impulse that is equal and opposite to the combined net impulse of the rest of the waveform used to achieve the color transition required for image update. However, the color rendering portion of the waveform must additionally overcome the state of the pigments induced by the phase of the first phase. As a result, the pigments do not begin the color update from a neutral state, but rather are initially driven in approximately the opposite direction from their desired final position. As a result, the total waveform can be quite long (on the order of several seconds).
[0047] For driving a multi-particle system, i.e. as described herein, the driving method typically involves applying voltages to first and second electrodes of a colour electrophoretic display, the first electrode forming the viewing surface of the display and the display having voltage control means capable of applying voltage differences of +VH, +VL, 0, -VL and -VH, respectively, between the first and second electrodes, where: +V H >+V L >0>-V L >-V H The driving method is as follows: (a) Between the electrodes, +V H or -V Hand displaying, at the viewing surface, alternating between the color of the fourth particles and the color of a mixture of the fourth particles and the second particles by applying a series of first pulses of a polarity that drives the fourth particles toward the first electrode, the series of first pulses being either +V L or -V L (b) applying a second pulse between the electrodes of +V H or -V H and displaying at the viewing surface an alternating color between the third particles and a mixture of the third particles and the second particles by applying a series of third pulses of a polarity that drives the third particles toward the first electrode, the series of third pulses being either +V L or -V L and alternating with a fourth pulse of opposite polarity but of longer duration.
[0048] The material from which the dielectric layer is made can be organic or inorganic. Preferably, the material should be impermeable to ions and electrons and have high dielectric strength (at least about 10 V / μm). The thickness of the dielectric layer depends on its dielectric constant, as discussed in more detail below. Examples of materials from which the dielectric layer can be made are silicon dioxide, silicon nitride, metal oxides (such as zinc oxide, tantalum oxide, hafnium oxide, and the like), and organic materials (such as parylene or other polymeric compounds). A combination of more than one material can be used, and the dielectric layer can comprise more than one sublayer, which can be of different materials.
[0049] As discussed above, the dielectric layer, in addition to blocking the electrochemical current through the display, also acts as a capacitor that can limit the build-up of residual voltage when the display is driven. Furthermore, when coupled with the correct drive / ground domains, electrophoretic displays can achieve much faster updates for color waveforms with only a marginal loss in overall color gamut.
[0050] A particular dielectric layer may be incorporated into an electrophoretic display at various locations relative to the electrophoretic medium, as shown in Figures 1A-1F. An electrophoretic display (101, 102, 103, 104, 105, 106) typically includes a top transparent electrode 110, an electrophoretic medium 120, and a bottom electrode 130, which is often a pixel electrode of an active matrix of pixels controlled with thin film transistors (TFTs). The electrophoretic medium 120 contains at least one electrophoretic particle 121, however, a second electrophoretic particle 122 or a third electrophoretic particle 123 or more are feasible. The electrophoretic medium 120 is typically so compartmentalized by the walls of a microcapsule 126 or microcell 127. A dielectric layer 140 may be disposed adjacent to either layer, however, typically adjacent to the electrode layer (110 or 130). More than one dielectric layer 140 may be present in a given electrophoretic display (105, 106), however only one layer is more common. The dielectric layer 140 may be of the type described below. The entire display stack is typically disposed on a substrate 150, which may be rigid or flexible. The displays (101, 102, 103, 104, 105, 106) also typically include a protective layer 160, which may simply protect the top electrode 110 from damage, or which may surround the entire display (101, 102) and prevent the ingress of water and the like. The electrophoretic displays (101, 102, 103, 104, 105, 106) may also include an adhesive layer 170 and a sealing layer 180, as required. In some embodiments, the dielectric layer 140 is disposed between the electrode layers (110, 130) and the adhesive layer 170, as in the displays shown in Figures 1C and ID. In some embodiments, the dielectric layer 140 is disposed above and below the electrophoretic medium 120, as shown in Figures 1E and 1F. The adhesive layer 170 may optionally be disposed between the dielectric layer 140 and the electrophoretic medium.In some embodiments (104, 106), adhesive layer 170 may include a primer component to improve adhesion to electrode layer 110, or a separate primer layer (not shown in FIGS. 1A-1F) may be used. (Electrophoretic displays and component part structures, pigments, adhesives, electrode materials, etc. are described in many patents and patent applications published by E Ink Corporation, such as U.S. Pat. Nos. 6,922,276, 7,002,728, 7,072,095, 7,116,318, 7,715,088, and 7,839,564, all of which are incorporated herein by reference in their entireties.)
[0051] The dielectric layers of the present invention may also be incorporated into electrowetting-on-dielectric (EWoD) devices, such as those used for electrowetting displays or "lab-on-a-chip" microfluidic devices. The basic operation of an EWoD device is illustrated in cross-section in FIG. 2. The EWoD 200 includes a cell filled with oil 202 and at least one aqueous droplet 204. The cell gap is typically in the range of 50-200 μm, although the gap can be larger. In the basic configuration, multiple driving electrodes 230 are disposed on one substrate, and a single top electrode 210 is disposed on the opposite surface, as shown in FIG. 2. The cell additionally includes a hydrophobic coating 207 on the surface that contacts the oil layer, and a dielectric layer 240 between the driving electrode 230 and the hydrophobic coating 207. (The top substrate may also include a dielectric layer, but is not shown in FIG. 2). The hydrophobic layer prevents the droplet from wetting the surface. When no voltage difference is applied between adjacent electrodes, the droplets maintain their ellipsoidal shape and minimize contact with hydrophobic surfaces (oil and hydrophobic layers). Because the droplets do not wet the surface, they are less likely to contaminate the surface or interact with other droplets (unless that behavior is desired).
[0052] While it is possible to have a single layer for both the dielectric and hydrophobic functions, such layers typically require a thick inorganic layer (to prevent pinholes) and a thick orientation layer has a resulting low dielectric constant, thereby requiring over 100V for droplet movement. To achieve low voltage actuation, it is more preferable to have a thin dielectric layer for high capacitance, free of pinholes, crowned by a thin organic hydrophobic layer. With this combination, it is possible to have electrowetting operation with voltages in the range of + / -10 to + / -50V, which is within the range that can be supplied by conventional TFT arrays. In some embodiments, the hydrophobic layer comprises a fluoropolymer, such as a perfluoropolymer, such as TEFLON-PTFE (polytetrafluoroethylene), TEFLON-AF (amorphous polytetrafluoroethylene copolymer), CYTOP (poly(perfluorobutenyl vinyl ether), or FULUOROPEL (perfluoroalkyl copolymer). Other newer hydrophobic coatings, such as those described in U.S. Pat. No. 9,714,463, may also be used. Typically, the hydrophobic layer is coated onto the dielectric layer by spin coating, however, other deposition methods such as slot or die coating, or spray coating may also be used.
[0053] When a voltage difference is applied between adjacent electrodes, the voltage on one electrode attracts the opposite charge in the droplet at the dielectric / droplet interface, and the droplet moves towards this electrode, as illustrated in Figure 2. The voltage required for acceptable droplet propulsion depends on the properties of the dielectric and hydrophobic layers. AC driving is used to reduce degradation of the droplet, dielectric, and electrodes by the various electrochemicals. The operating frequency for EWoD can be in the range of 100 Hz to 1 MHz, although lower frequencies at or below 1 kHz are also preferred for use with TFTs, which have limited operating speed.
[0054] As shown in Figure 2, the top electrode 210 is a single conductive layer that is typically set to zero volts or a common voltage value (VCOM) to account for offset voltages on the drive electrodes 230 due to capacitive kickback from the TFTs used to switch the voltage on the electrodes (see Figure 3). The top electrode can also have a square wave applied to increase the voltage across the liquid. Such an arrangement allows a lower drive voltage to be used for the TFT-connected drive electrodes 230 because the top plate voltage 210 is additive to the voltage supplied by the TFT.
[0055] As shown in Figure 3, an active matrix of propulsion electrodes can be arranged to be driven with data lines and gate (select) lines, similar to an active matrix in an electrophoretic or liquid crystal display. The gate (select) lines are scanned for addressing one line at a time, while the data lines carry voltages to be delivered to the propulsion electrodes for electrowetting operations. If no movement is required or if the droplet is intended to move away from a propulsion electrode, 0V is applied to that (non-target) propulsion electrode. If the droplet is intended to move towards a propulsion electrode, an AC voltage is applied to that (target) propulsion electrode.
[0056] One embodiment of a dielectric layer 440 of the present invention is shown in FIG. 4 and disposed on a substrate 450. The dielectric layer includes a first "barrier" layer 441, a second "thick" layer 442, and a third "capping" layer 443. The first layer 441 includes aluminum oxide or hafnium oxide and has a thickness of 9 nm to 80 nm. The second layer 442 includes tantalum oxide or hafnium oxide and has a thickness of 40 nm to 250 nm. The third layer 443 includes tantalum oxide or hafnium oxide and has a thickness of 5 nm to 60 nm. Typically, the second layer and the third layer comprise different materials, for example, the second layer may comprise primarily hafnium oxide while the third layer comprises primarily tantalum oxide. Alternatively, the second layer may comprise primarily tantalum oxide while the third layer comprises primarily hafnium oxide. In a preferred embodiment, the first layer is aluminum oxide. In a preferred embodiment, the first layer is 20-40 nm thick, while the second layer is 100-150 nm thick, and the third layer is 10-35 nm thick. The thicknesses of the various layers can be measured using a variety of techniques, including, but not limited to, scanning electron microscopy, ion beam backscattering, x-ray scattering, transmission electron microscopy, and ellipsometry. The resulting dielectric layer 440 is flat, pinhole free, and chemically resistant.
[0057] The dielectric layer 440 as shown in FIG. 4 can be directly coated on any type of substrate compatible with the first layer 441 and the conditions required to deposit the first layer (discussed below). The dielectric layer 440 can be coated, for example, on the pixel electrodes 430 of an active matrix as shown in FIG. 5. The dielectric layer 440 can be coated on a printed circuit board or other microfabricated structure. In addition, the third layer 443 can be coated with a hydrophobic layer 407 for use in electrowetting applications as discussed above with respect to FIG. 2. Such a combination of the dielectric layer 440 and the hydrophobic layer 407 is preferably reasonably thin, i.e., less than 600 nm thick, e.g., less than 400 nm thick, e.g., less than 300 nm thick. The lower bound for a three-layer dielectric stack with a hydrophobic coating is greater than 60 nm thick, e.g., greater than 100 nm thick, e.g., greater than 150 nm thick.
[0058] A method for making a dielectric layer of the present invention is described with respect to FIG. 6. In an initial step 610, a substrate is provided on which a dielectric stack is coated. The substrate is typically cleaned, for example with ethanol or isopropyl alcohol, prior to coating. The substrate can be any material, provided that the material is stable during the atomic layer deposition (ALD) and sputtering steps described below. For example, the substrate can be a printed circuit board, coated glass, for example ITO coated glass, or an active matrix TFT backplane microfabricated on glass or other substrate material. The next step 620 is to deposit a first layer on the substrate using atomic layer deposition, typically plasma-assisted ALD or (thermal) water vapor-assisted ALD. For example, a first layer of aluminum oxide can be processed using trimethylaluminum (Al(CH3)3) or Ta[(N(CH3)2)3NC(CH3)3] in conjunction with oxygen plasma at a substrate temperature of about 180° C. and low pressure (less than 100 mbar). Alternatively, the aluminum oxide layer can be deposited using a trimethylaluminum-water process. Atomic layer deposition can be performed at a rate of more than 0.1 nm / min, for example, 0.2 nm / min or more. The final thickness of the aluminum oxide or hafnium oxide is typically 9 nm to 80 nm thick. Details of these ALD processes are described by Bent and coworkers in "A brief review of atomic layer deposition: from fundamentals to applications", Materials Today , (2014), vol. 17, No. 5, p. 236-46 (incorporated herein by reference in its entirety).
[0059] Once the first ALD layer has been applied to the substrate, the resulting coated substrate is sputtered, such as by magnetron sputtering, to produce a second, thicker layer in a third step 630. Typically, the second, thicker layer is primarily tantalum oxide or hafnium oxide. The sputtering process is carried out at room temperature in a mixed oxygen-argon atmosphere, and the sputtering target is a stoichiometric oxide of tantalum or hafnium, or a metallic tantalum or metallic hafnium target. The resulting sputtered tantalum oxide or hafnium oxide layer has a thickness of 40 nm to 250 nm. Magnetron sputtering is preferred, but other forms of sputtering, such as ion sputtering or plasma sputtering, may also be used. Sputtering may be carried out at a rate of more than 0.5 nm / min, such as at or above 1 nm / min, such as at or above 2 nm / min. For more information on these processes, see Kelly and Arnell, "Magnetron sputtering: a review of recent developments and applications," Vacuum 56 (2000) 159-172, which is incorporated herein by reference in its entirety. Although the sputtering process is typically carried out in a separate sputtering chamber, the method of the present invention may also be accomplished in a single reactor capable of both atomic layer deposition and sputtering deposition.
[0060] After the sputtering step 630 is completed, the resulting substrate with the ALD layer and the sputtered layer undergoes a second atomic layer deposition step 640. Typically, this second ALD step is performed using plasma-assisted ALD with Ta[(N(CH3)2)3NC(CH3)3] or Hf(N(CH3)2)4 to produce a layer of tantalum oxide or hafnium oxide 5 nm to 60 nm thick. Like the first ALD step 620, the second ALD step 640 is also performed at a substrate temperature of 150-190°C and low pressure (less than 100 mbar). After completion of this second ALD step 640, a substrate with a high-k stack (650) is produced. The final high-k coating is typically 100-700 nm in total thickness with a combined dielectric strength of 6MV / cm or greater. The high-k stack is also remarkably smooth and nearly pinhole-free, as shown in the following examples.
[0061] Although not explicitly shown in Figure 6, the final high-k stack may be coated with a hydrophobic layer, for example, using spin coating as described above. Such a combined high-k stack with a hydrophobic coating is particularly useful for electrowetting applications, such as for electrowetting displays and microfluidic applications. EXAMPLES
[0062] Fabrication and characterization of Al2O3 / Ta2O5 / Al2O3 stacks A high-k dielectric stack was fabricated using the technique described above with respect to FIG. 6. An initial substrate of ITO-coated glass (Sigma-Aldrich) was coated with 25 nm of Al2O3 using oxygen plasma ALD using a Veeco / CNT Fiji F200 with a total deposition time of about 115 minutes and a substrate temperature of 180° C. The substrate with deposited Al2O3 was removed from the reactor and imaged using a Bruker Dimension Icon atomic force microscopy tool. The image captured by the AFM instrument is shown in the bottom right of FIG. 7. An exemplary surface roughness measurement at the dotted line across the AFM image is shown in the bottom graph of FIG. 8. As expected, the first ALD step achieves a surface with little height variability.
[0063] Following deposition of 25 nm of Al2O3 and imaging with AFM, the substrate was placed in a magnetron sputtering chamber Kurt Lesker LAB Line Sputter Deposition Tool and 70 nm of Ta2O5 was deposited using a metal tantalum sputtering target in an oxygen-argon environment for approximately 30 minutes. After sputtering was completed, the resulting coated substrate was again imaged with AFM, as shown in the right center image of FIG. 7 and the center graph of FIG. 8. Notably, the surface variations were much larger after sputtering, and ridges began to appear across the coated surface. However, using sputtering, the dielectric layer was made nearly three times thicker in less than half the time of the previous ALD step.
[0064] Finally, after the sputtering step, the substrate was placed back into the ALD machine and the Al2O3 process was repeated accordingly (but for only about 70 minutes), resulting in an Al2O3 / Ta2O5 / Al2O3 stack (i.e., with a 25 nm base layer, a 70 nm center layer, and a 15 nm capping layer) as shown in FIG. 7. The resulting three-layer stack was then imaged using AFM to produce the image shown in the top right of FIG. 7. Again, an example line profile (dashed line) is shown as the top graph in FIG. 8. It is noteworthy that a certain amount of surface roughness from the sputtering process was smoothed with the application of the second ALD layer, however, some of the bumps generated by the sputtering process are still present. After imaging, the resulting Al2O3 / Ta2O5 / Al2O3 stack was evaluated for pinholes by electroplating copper onto the dielectric layer using a copper sulfate solution. The stack showed only very little leakage current after electroplating, suggesting that very few pinholes were present in the dielectric layers, which was additionally verified by optical microscopy (not shown).
[0065] It is possible to model the response of electrophoretic displays both without (FIG. 9A) and with (FIG. 9B) a dielectric layer as described herein. As shown in FIGS. 9A and 9B, an electrophoretic display "stack," which includes a dielectric layer between the electrophoretic medium and the top electrode as in FIG. 1B, can be modeled as a series of Voigt elements, i.e., having both resistance (R) and capacitance (C) in a parallel arrangement, thereby allowing calculation of the voltage response of each component when the stack is driven by a waveform ("stack" in FIGS. 10A and 10B). Although it is obvious that simple linear models are gross simplifications of the electrical behavior of actual electrophoretic displays, they are useful for demonstrating the advantages of incorporating a dielectric layer into an electrophoretic display, especially when the display is driven with a waveform that is not impulse balanced.
[0066] 9A and 9B, a typical electrophoretic fluid (hereafter, the "internal phase") comprising a solvent with a low dielectric constant (around 2) has a dielectric constant of 0.02-5 nF / cm when incorporated into a compartment with a thickness in the range of 10-25 microns. 2 and bulk capacitance "C1" in the range of about 1 to 10 MΩ cm 2 The capacitance at the interface between the electrophoretic fluid and the other layers that make up the display (collectively referred to as the "external phase") is more difficult to estimate, but can be approximated by combining two capacitors in series, with the dielectric thickness of each approximated by the Debye length in each medium (i.e., the internal and external phases). This is around 10-100 nF / cm 2 gives an estimate for C2 of 100 kΩ. The interfacial resistance R2, which corresponds to the passage of ions across the boundary, is also difficult to estimate. If this resistance is too high, the display will exhibit complete electrical (and possibly optical) kickback (where a pixel reverts to half its previous state after an update has been completed). The value of R2 that gives the best match with current measurements when driving a typical display is approximately the same as the resistance of the external phase, i.e., 1-10 MΩ cm 2 The bulk capacitance C3 of the external phase is in the range of about 0.1 to 10 nF / cm, assuming that the external phase comprises a polymeric material containing mobile ions with a dielectric constant of about 10. 2 The resistance of the external phase, R3, is estimated to be 1 to 10 MΩ cm 2 Finally, the interfacial capacitance C4 at the electrode boundary is estimated from the Debye length in the doped polymer external phase. Its conductivity is almost identical to that of the internal phase, but the mobility of the charge carriers is much lower, since the viscosity of the polymer is several orders of magnitude higher than that of the electrophoretic solvent. As a consequence, the concentration of ions is much higher in the external phase than in the internal phase, and, consequently, the Debye length must be much shorter. The interfacial capacitance is in the range of 2-20 μF / cm 2, i.e., much larger than any other capacitance in the system. It is possible that the electrochemical reaction at this interface may generate a "resistance" path, illustrated diagrammatically as R4 in FIG. 9A, which is not a simple resistor. This path is undesirable as it may lead to eventual degradation of the electrode as explained above. Methods for mitigating electrochemical currents in electrophoretic displays are discussed in detail, for example, in U.S. Pat. No. 9,726,957, which is incorporated herein by reference in its entirety.
[0067] The time required to generate an image (known as the update time) is related to the RC time constant for charging capacitor C2, which is typically less than one second. However, the RC time constant for charging C4 is much longer than this, typically on the order of 100 seconds, and therefore C4 is only partially charged in the time that C2 is fully charged. Thus, in this model, the voltage across C4 is an approximation of the "residual voltage" stored in the display. In a DC balanced waveform, this residual voltage is largely reduced during the process of updating. However, in a non-DC balanced waveform, the residual voltage is not reduced and can build up on the system. Because the RC time for charging and discharging C4 is so long, it is not practical to fully discharge the C4 capacitor by grounding the display. To make matters worse, if there is a possibility of discharging C4 due to the electrochemical reaction shown as R4 in FIG. 9A, there may also be slow electrochemical degradation of the electrodes in the undriven display caused by the residual voltage after updating. Such electrochemistry is irreversible and leads to degradation of performance and ultimately failure of the display.
[0068] FIG. 9B shows how the model can be adjusted to accommodate an added dielectric layer that provides capacitance C5 in accordance with the present invention. It can be seen that resistive element R4 has been omitted from the representation of the electrode interface. Since the dielectric layer separates the electrodes from the external phase, there is no possibility of electron transport here. Capacitors C4 and C5 are in series, and therefore the RC constant for the build-up of the residual voltage is lower than in the case shown in FIG. 9A, which lacks capacitor C5. The RC time constant for the build-up and discharge of the residual voltage is shorter when C5 is included, making it more practical to directly discharge the residual voltage within a reasonable time. Such discharge can be accomplished, for example, using the methods and circuits described in U.S. Pat. No. 10,475,396, which is incorporated herein by reference in its entirety.
[0069] 10A and 10B show the calculated voltages across various Voigt elements in the model circuits of FIGS. 9A and 9B using typical color-forming waveforms. The equilibrium residual voltages at each component after driving with the waveform "stack" are shown. (V1 corresponds to component 1 with R1 and C1, etc.) Comparing the curves in FIGS. 10A and 10B, the model predicts that in the model system including the dielectric layer, the same long-term residual voltages can be roughly obtained using much shorter discharge times, i.e., a 3.5 second discharge for model circuit 2 (FIG. 9B) and an 8 second discharge for model circuit 1 (FIG. 9A). EXAMPLES
[0070] Changes in color gamut due to dielectric layers The addition of capacitance C5 to the dielectric layer, as illustrated in the model circuit, can be expected to slightly change the voltage in the imaging layer of the display, affecting the number of colors that can be achieved. The amount of color lost due to this voltage drop was experimentally verified using a four pigment (CMYW) test cell that includes silicon nitride layers of different thicknesses across the rear electrode of the display. Details of the test cell can be found in U.S. Patent No. 9,921,451, which is incorporated herein by reference in its entirety. The results are shown in Table 1 below. Table 1. Effect of silicon nitride dielectric on the color gamut of a four-particle (CMYW) electrophoretic medium in a test cell. [Table 1]
[0071] Table 1 shows the estimated capacitance of the dielectric based on the measured thickness, and the color gamut of the display as measured by applying a series of test waveforms and measuring with a calibrated color sensor. The color gamut was greatest without the dielectric, but was suitable for most purposes when the silicon nitride was in the range of 10-50 nm.
[0072] To assess the likelihood of undesirable electrochemistry and kickback, residual voltage build-up was measured in the test displays of Table 1. To assess residual voltage build-up, each display was addressed with a series of impulses whereby a positive voltage pulse was applied to the test display for a time T_V, and then the device was grounded for a time T_ground. The relative amount of impulse time and ground time can be expressed as a duty cycle. After the ground period, each test display was allowed to float for a time T_float. The voltage across the display electrodes during T_float was measured. This pattern was repeated multiple times and recorded for each test display using electronic test equipment.
[0073] 11A-11C show the results for various ground times where the applied test voltage was 1V and T_V was 1 second. In FIG. 11A, the ground time was zero, i.e., 100% duty cycle. In FIG. 11B, the ground time was 1 second, i.e., 50% duty cycle. In FIG. 11C, the ground time was 3 seconds, i.e., 25% duty cycle. For each waveform, the measured remnant voltage is presented as a curve on the graph. As a reminder, the steeper curve corresponds to the SiNi dielectric layer, while the more gentle curve corresponds to the test display without the SiNi dielectric layer. Furthermore, looking at FIG. 11B and FIG. 11C, the measured remnant voltage levels roughly corresponded to the thickness of the SiNi layer, in that the thinnest SiNi layer resulted in the highest remnant voltage and the thickest SiNi layer resulted in the lowest remnant voltage. Notably, for a 25% duty cycle (drive / ground), both the 50 nm SiNi layer and the 75 nm SiNi layer achieved a remnant voltage below that of the non-blocking layer within 100 seconds. Furthermore, when discharge of the remnant voltage is enabled by grounding between applied voltage pulses, the final equilibrium remnant voltage is the lowest in the module with the thickest dielectric layer (i.e., the smallest capacitance C5 in FIG. 9B). This result is surprising because it suggests that when the correct drive / ground duty cycle is combined with the correct dielectric layer, both the electrophoretic response time and the overall remnant voltage can be simultaneously reduced. EXAMPLES
[0074] Reducing electrochemical degradation in electrophoresis test cells In addition to improving the response of the electrophoretic medium (above), the effect of the added dielectric layer on the lifetime of the test displays was also evaluated. Two test displays of approximately 8" diagonal were prepared using the CMYW4 particle electrophoretic medium of Example 2. The control used a standard active matrix TFT backplane such as found in commercial electronic readers. In the other test display, the pixel electrodes were coated with 30 nm of tantalum oxide. The continuity of the tantalum oxide layer was not perfect, as shown in the graph of FIG. 12. If the tantalum oxide was free of pinholes or defects, it would be expected that there would be significantly less resistive current density relative to a tantalum oxide "blocking" backplane. The displays were driven in an advanced DC unbalanced manner using the sequence: (a) 30V for 3 seconds, then (b) grounded for 20 ms, then (c) floated for 6 seconds. This test cycle was repeated several times. Despite the shortcomings of the tantalum oxide coating, after four hours of drive there was a noticeable difference in the "yellowing" of the white state in the test pattern when the displays were compared side-by-side. The difference in the amount of yellowing was even more noticeable after an additional four hours of drive. Thus, in the presence of a highly DC unbalanced waveform, the display with the tantalum oxide coated backplane showed evidence of undergoing less electrochemical degradation.
[0075] Thus, a robust and non-reactive high-k dielectric layer can be formed. It will be apparent to those skilled in the art that numerous changes and modifications can be made in the specifically detailed embodiments of the invention described above without departing from the scope of the invention. Therefore, the entirety of the foregoing description should be interpreted in an illustrative rather than a limiting sense.
Claims
[Claim 1] The invention as depicted in the drawings of this application.
Citation Information
Patent Citations
Display panel and front plate for display panel
JP2003270673A
Display
JP2009229741A
colored electrophoretic display
JP2017526980A
Bistability enhancement in total internal reflection image display
JP2018527617A
Electrophoretic Display Device
KR100731863B1